2021
DOI: 10.9734/jabb/2021/v24i930241
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals (Lead, Zinc, Nickel and Cadmium) in Medicinal Plants (Scent Leaf and Pawpaw) in Bayelsa State, Nigeria

Abstract: Aims: This study investigated the level of zinc, nickel, lead and cadmium in selected medicinal plants - Scent Leaf (Ocimum gratissimum) and Pawpaw (Carica papaya) that are traditionally used in alternative medicine in Amassoma community, Bayelsa State, Nigeria. Study Design: Scent leaf (Ocimum gratissimum) and Pawpaw (Carica papaya) from where these plants are grown were randomly collected for heavy metal analysis from within Amassoma community in Southern Ijaw Local Government Area of Bayelsa State, Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Previous studies have observed that papaya plants have reached TF > 1 value for metals such as Cd, Pb and Zn, indicating that they have bioaccumulation capacity (Akintan et al, 2019). It has also been reported that papaya plant has been considered as an indicator of heavy metal contamination based on tree bark samples (Chukwuka & Uka, 2013), where it has been found that they can absorb elements such as Cd, Pb, Cu, Ni and Zn with the ability to translocate to aerial organs (Assayomo et al, 2021;Eludoyin & Gafar, 2020). Meng et al (2019) have reported that papaya fruit can accumulate heavy metal concentrations above the maximum permissible limits set by WHO with a potential health risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed that papaya plants have reached TF > 1 value for metals such as Cd, Pb and Zn, indicating that they have bioaccumulation capacity (Akintan et al, 2019). It has also been reported that papaya plant has been considered as an indicator of heavy metal contamination based on tree bark samples (Chukwuka & Uka, 2013), where it has been found that they can absorb elements such as Cd, Pb, Cu, Ni and Zn with the ability to translocate to aerial organs (Assayomo et al, 2021;Eludoyin & Gafar, 2020). Meng et al (2019) have reported that papaya fruit can accumulate heavy metal concentrations above the maximum permissible limits set by WHO with a potential health risk.…”
Section: Discussionmentioning
confidence: 99%